Writing in French Izzet Melih Devrim (1887-1966) and his Leila (1912) - Ozturk, Banu (AMSTERDAM UNIV PRESS, 2017)
Izzet Melih was an Ottoman author who lived during the final days of the Ottoman Empire. Born in Jerusalem in 1887, he spent the most of his life in Istanbul and, like many intellectuals of that time was scholar at Galatasaray High School, following the French educational model. He began from a young age to publish prose poetry, short stories, literary reviews and criticism in Istanbul (in Cocuklara Mahsus Gazete ('Children's Newspaper'), Mecmua-i Edebiye ('Literary Magazine'), in bilingual magazines (Levant Herald and Stamboul), and in French magazines such as La Revue de France. Izzet Melih also wrote a play in French, Leila, which was first published in France in 1912. This chapter analyses this interesting example, considering why Melih preferred writing in French, pursuing the relationship and/or lack of relationship between his 'self' and his choice of writing in French with this 'self'.
Keywords: Modern Turkish Literature; Ottoman Theatre; Izzet Melih devrim; Leila; Writing in French; History; Linguistics